Pemanfaatan Penilaian Portofolio sebagai Instrumen Evaluasi Otentik dalam Pembelajaran untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa - Jidro Alfindo Sabuin; Rani Yuniati Naek (Indo Publishing, 2026)
This study aims to examine the use of portfolio assessment as an authentic evaluation instrument in the learning process to improve students’ activeness and learning outcomes. Portfolio assessment is an assessment method that emphasizes the process of students’ learning development through collections of assignments, students’ work, activity records, and learning reflections arranged systematically and continuously. Through this assessment, students are given the opportunity to demonstrate their abilities, creativity, and learning progress more comprehensively.The method used in this study is a literature review by utilizing various scientific sources such as books, journals, articles, and previous studies related to portfolio assessment and authentic evaluation in learning. The collected data were analyzed descriptively to determine the effectiveness of implementing portfolio assessment in teaching and learning activities.The results of the study indicate that the implementation of portfolio assessment can increase student participation in learning, foster responsibility toward assignments, develop creativity, and train reflective thinking skills. In addition, portfolio assessment helps teachers evaluate students’ learning development more comprehensively and objectively because it focuses not only on final results but also on the learning process experienced by students. Therefore, portfolio assessment can be used as an effective alternative authentic evaluation method to support the improvement of learning quality and student learning outcomes in schools.